Library data labs: using an agile approach to develop library analytics in UK higher education. Issue 1 (8th January 2018) - Burke, Siobhán; MacIntyre, Ross; Stone, Graham
Abstract : Purpose: The purpose of this paper is to give an overview of the Jisc and Higher Education Statistics Agency (HESA) Library Data Labs project and its outputs. This collaboration involved bringing together cross-institutional library teams to produce proof of concept data-visualised dashboards using library analytics data that could be made available to others via the Heidi Plus service. Design/methodology/approach: The teams used an agile approach, which adapted the agile methodology for non-technical and disparate team members. The key agile elements were followed, including the Scrum approach, whereby teams had a product owner, several development team members, a data wrangler and a scrum master. Many of the dashboards took inspiration from some of the earlier Jisc work on library analytics. Findings: A wide variety of proof of concept dashboards were created addressing a range of library issues. These fell into two main categories for the cross-institutional teams, namely, comparing the Society of College, National and University Libraries (SCONUL) annual statistics results against the National Student Survey (NSS) data and collection management and analysis. Research limitations/implications: Some of the HESA data were potentially sensitive. In effect, this created a walled garden as some of the data were not designed for sharing. Furthermore, the data that the Jisc team used were restricted by publisher agreements, meaning that specific institutions' usage could not be identified to others. Originality/value: The paper provides insight into the Library Data Labs project and discusses a number of implications from the outcomes of the project. These are now being investigated by HESA, Jisc and individual institutions.